Sistem Informasi Donor Darah dengan Penerapan Rapid Application Development Menggunakan Notifikasi Whatsapp di Kabupaten Ogan Komering Ilir - Febriyanti, Valentina; Aryanti, Aryanti; Halimatussa’diyah, R. A. (Program Studi Teknik Informatika Universitas Pamulang, 2024)
The Indonesian Red Cross of Ogan Komering Ilir Regency is a humanitarian organisation established to help alleviate the suffering of others. PMI’s activies are synonymous with humanitarian activities, such as blood donation. Currently, the donor data input system is still done manually by entering data into a ledger and there is no reminder information system for donors. Based on the above problems, this research aims to design an information system for donors using whatsapp notifications appling the Rapid Application Development method. To test result of the data this study using blackbox and the data that has been entered has been in accordance with expectations.